Soviet poetry in 1926 in the light of writers’ and readers’ opinion surveys - Павловец, Михаил (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The article researches the issue of the relevance of poetry in the USSR, using as an example the year 1926, when several literary periodicals simultaneously decided to investigate the attitude of their readers and of poets towards this issue. The analysis of the surveys conducted among readers and in libraries confirms the statement made by Boris Pasternak that lyric poetry was then undergoing a crisis, caused by the loss of its past audience and by not yet having any new audience who would need the subjectivity of an author to be presented to tchem in a lyrical form.